Instytucjonalna współpraca biskupów w wymiarze ponaddiecezjalnym - Dyduch, Jan (Analecta Cracoviensia, 2008)
The Church’s teaching concerning community between Herself and the College of Bishops, which was considerably broadened by Vatican II, is the foundation of their varied and diversified collaboration.This collaboration also manifests itself in such over diocesan institutions as Episcopal Conferences, regional convocations as well as the structure of the Church metropolis itself.The post-Vatican II legislation has reshaped and ascribed new tasks to all the above mentioned institutions. Owing to that fact they can be an efficient instrument of the over diocesan ministry.